EFFECT OF WORKABILITY AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT BAPPEDA ACEH JAYA DISTRICT - Juned, Vilzati; Sanjaya, Jenian; Ikhbar, Samsul (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study was to determine the effect of workability and leadership style simultaneously on the performance of Bappeda employees of Aceh Jaya Regency, then to determine the effect of workability and leadership style partially on the performance of Bappeda employees of Aceh Jaya Regency. The location of the research was carried out at the Bappeda of Aceh Jaya Regency. The object of research is the problem of providing work skills and leadership styles as well as employee performance at Bappeda Aceh Jaya Regency. Data analysis equipment used in this study is multiple linear regression. Simultaneous research results show that the test results simultaneously obtained the F-count value of 30.429, while Ftable at the significance level️= 5% is equal to 3,267. This shows, based on the calculation of the statistical test F-count shows that F-count > Ftable, with a probability level of 0.000, that the employee's workability and leadership style affect improving the performance of Bappeda Aceh Jaya Regency employees, while the results of the study partially show that the provision of work skills and leadership style affects the performance of Bappeda Aceh Jaya district employees. To improve the performance of employees at the Bappeda of Aceh Jaya Regency, the factor of providing employee work skills should be one of the priorities for improving employee performance and the distribution of appropriate leadership styles.